New Formulation-Microporation Combination Approaches to Delivering Ciclopirox across Human Nails - Juliana Kishishita; Camila de Almeida Perez Pimenta; Danielle Patricia Cerqueira Macedo; M. Begoña Delgado-Charro; Leila Bastos Leal (MDPI AG, 2024)
Topical treatments for onychomycosis are of interest to those seeking to avoid systemic drug interactions and to improve systemic safety. This work aimed to develop aqueous-based, simple, and cost-effective vehicles that provide high solubility for ciclopirox and enable the delivery of an active through channels created by nail microporation. Following solubility tests, aqueous gels and thermogels based on hydroxypropylmethylcellulose and poloxamer 407, respectively, were loaded with 8% and 16% ciclopirox. Their performance was then compared to the marketed lacquer Micolamina® in in vitro release tests with artificial membranes and in in vitro permeation tests with human nail clippings with and without poration. Finally, a microbiological assay compared the best gel formulations and the reference product. Little correlation was observed between the in vitro release and the permeation data, and the drug release was highly membrane-dependent. Ciclopirox nail retention in single-dose, porated nails tests was larger than in daily-dosing, non-porated nail conditions. The series of new gel and thermogel vehicles delivered ciclopirox more effectively than Micolamina® in single-dose, porated nail experiments. The inhibition of Trichophyton rubrum activity was significantly increased with microporated nails when the gel formulations were applied but not with Micolamina®. Overall, the results suggest that the new vehicles could be successfully combined with nail microporation to improve the drug delivery and efficacy of topical antifungal medication while reducing the dosing frequency, facilitating patients' adherence.